Radion Production in External Electromagnetic Field - Dong, Phung Van; Long, Hoang Ngoc; Thao, Nguyen Huy; Soa, Dang Van; Hau, Nguyen Thi (Communications in Physics, 2011)
A review of Randall-Sundrum model with stressing on radion phenomenology is presented. The radion production in the external electromagnetic field is considered. The total cross sections for the conversions in the presence of the electric field of the flat condenser as well as in the magnetic field of the solenoid are calculated in details. Based on our results a laboratory experiment for production and detection of the light radions may be described.